Exploring Teachers' Digital Competencies in Secondary Schools: A Systematic Literature Review - Amilusholihah, Amilusholihah; Ahman, Eeng; Kurniawati, Susanti; Sutarni, Nani; Sari, Rafita (Electronic Journal of Education, Social Economics and Technology, 2024)
Teacher Digital Competence (TDC) is crucial for secondary school teachers who facilitate interactive, adaptive learning environments to achieve Sustainable Development Goal (SDG) 4 on Quality Education. This research aims to systematically elucidate TDC at the secondary school level. In order to address the research questions, guidelines from PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) were employed to systematically identify 30 out of 450 articles, spanning the period from 2020 to 2024, and retrieved from three databases, namely Scopus, WoS, and ERIC, in accordance with the established exclusion and inclusion criteria. The results show that (1) Interest in teachers' digital competence surged in 2024, reflecting the educational sector's post-pandemic priorities. Key studies from Australia, Spain, and Switzerland have led influential contributions to educational technology, highlighting the global importance of this field. (2) Essential strategies for improving digital competence include targeted professional development, effective integration of technology in classrooms, and adherence to international standards. (3) Teachers face challenges such as limited training and institutional support, underscoring the need for structured programs to enhance digital skills. (4) Frameworks like DigCompEdu, TPACK, TAM and ISTE have proven effective for assessing and strengthening digital competence to teaching practices and (5) TDC is effective in improving student learning outcomes. Future research should delve deeper into the factors that influence teachers' digital competence and explore frameworks that can be adapted to different educational contexts.